2011
DOI: 10.1165/rcmb.2010-0035oc
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of NF-κB and Hypoxia-Inducible Factor−1 byS-Nitrosoglutathione Does Not Alter Allergic Airway Inflammation in Mice

Abstract: Induction of nitric oxide synthase (NOS)-2 and production of nitric oxide (NO) are common features of allergic airway disease. Conditions of severe asthma are associated with deficiency of airway S-nitrosothiols, a biological product of NO that can suppress inflammation by S-nitrosylation of the proinflammatory transcription factor, NF-kB. Therefore, restoration of airway S-nitrosothiols might have therapeutic benefit, and this was tested in a mouse model of ovalbumin (OVA)-induced allergic inflammation. Naive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
15
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 62 publications
3
15
0
Order By: Relevance
“…In addition, it appears that NOS2 may also function constitutively to maintain basal lung SNOprotein levels, since NOS2 Ϫ/Ϫ mice exhibited substantially lower SNO-p65 levels at baseline compared with WT controls (Fig. 5), which is consistent with recent findings by Olson et al (30). In this regard, we are currently attempting to elucidate the mechanisms responsible for basal airway/lung SNO maintenance and LPS-induced denitrosylation.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…In addition, it appears that NOS2 may also function constitutively to maintain basal lung SNOprotein levels, since NOS2 Ϫ/Ϫ mice exhibited substantially lower SNO-p65 levels at baseline compared with WT controls (Fig. 5), which is consistent with recent findings by Olson et al (30). In this regard, we are currently attempting to elucidate the mechanisms responsible for basal airway/lung SNO maintenance and LPS-induced denitrosylation.…”
Section: Discussionsupporting
confidence: 86%
“…The results of the present study extend these observations to a mouse model of lung injury supporting an anti-inflammatory role for NOS2 in the lung via inhibition of NF-B. Of note, NOS2 deficiency was recently demonstrated to increase NF-B activity and modestly augment allergic airway inflammation in a mouse model of asthma, although mechanistic correlation to S-nitrosylation of p65 was equivocal (30).…”
Section: Discussionsupporting
confidence: 72%
“…The uncoupling of airway inflammation and AHR in the OVA model with GSNO therapy is not entirely unexpected, since we previously found that GSNOR-deficient mice are protected from AHR and have elevated lung SNO content compared with WT control littermates despite no apparent changes in inflammation (32). In addition, a recent report by Olson et al (31) likewise did not support an anti-inflammatory role for GSNO in suppressing markers of inflammation or mucus metaplasia in an allergic airway model, even though the levels of active nuclear factor kappa b (NF-B), a target of S-nitrosylation (20,28), were reduced by GSNO in the lung. This discordance between proinflammatory cytokines and other markers of allergic inflammation may result from other compensatory effects of GSNO.…”
Section: Discussionmentioning
confidence: 68%
“…In order to explore the biological significance of JFK-mediated ING4 degradation, we analyzed the cellular signaling transduction pathways that are potentially influenced by JFK using the Human Signal Transduction PathwayFinder PCR array (SABioscience) (Hager-Theodorides et al 2009;Olson et al 2011). This array profiles the expression of ∼100 key genes representing 10 prominent cellular signal transduction pathways, including TGF-β, WNT, NF-κB, JAK/STAT, p53, Notch, Hedgehog, PPAR, oxidative stress, and hypoxia pathways.…”
Section: The Jfk-ing4 Pathway Intersects With Nf-κb Signalingmentioning
confidence: 99%